2017
DOI: 10.1038/s41598-017-18119-x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of music and prefrontal cortex stimulation in modulating response inhibition

Abstract: Influential hypotheses propose that alterations in emotional state influence decision processes and executive control of behavior. Both music and transcranial direct current stimulation (tDCS) of prefrontal cortex affect emotional state, however interactive effects of music and tDCS on executive functions remain unknown. Learning to inhibit inappropriate responses is an important aspect of executive control which is guided by assessing the decision outcomes such as errors. We found that high-tempo music, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
53
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 75 publications
6
53
0
Order By: Relevance
“…These variabilities in the outcome of exposure to music might be related to the multifaceted effects of music on various brain functions. Executive control describes brain mechanisms that optimize the use of cognitive abilities for achieving goals (Mansouri et al, a; Mansouri et al, b; Mansouri et al, ; Mansouri, Rosa, & Atapour, ). Working memory and inhibition of inappropriate behavior are important aspects of executive control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These variabilities in the outcome of exposure to music might be related to the multifaceted effects of music on various brain functions. Executive control describes brain mechanisms that optimize the use of cognitive abilities for achieving goals (Mansouri et al, a; Mansouri et al, b; Mansouri et al, ; Mansouri, Rosa, & Atapour, ). Working memory and inhibition of inappropriate behavior are important aspects of executive control.…”
Section: Introductionmentioning
confidence: 99%
“…Background music also affects the emotional state, mood, and arousal in humans and therefore the behavioral and cognitive effects of music might emerge as a result of such changes in mood and emotional state (Jäncke, ; Koelsch, ; Krumhansl, ; Suda, Morimoto, Obata, Koizumi, & Maki, ). On the other hand, music might also directly engage brain regions that are involved in perceptual, mnemonic and executive control of behavior (Li, Chen, & Tsai, ; Mansouri et al, a; Schmithorst, ). A better understanding of music effects in humans and other species requires dissociating the effects of various contextual factors, which might interact with music in modulating the cognitive functions.…”
Section: Introductionmentioning
confidence: 99%
“…The somatic marker hypothesis postulates that alterations in emotional regulation and arousal state may influence the decision-making process (Bechara et al, 1999, 2005). In this context, conflict and its associated cognitive difficulty or uncertainty might induce emotional state change with concomitant autonomic and somatic responses and consequently influence executive functions and conflict resolution (Mansouri et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that contextual factors with emotional content might convey emotional information and influence cognitive functions, particularly when resolving conflict requires recruitment and allocation of executive control (Mansouri et al, 2017a). Such an interaction between emotional regulation and cognitive control might influence the ability to resolve the conflict.…”
Section: Introductionmentioning
confidence: 99%
“…Making music involves the brainstem, limbic systems and frontal lobes (Alluri et al, 2011; Meyer et al, 2014), stimulates the visual- and motor cortex (Collins, 2013), and leads to volume- and activity increases of the corpus callosum (Schlaug et al, 1995; Steele et al, 2013). A growing number of studies suggest that many brain areas involved in attention processes are activated by music (Schmithorst and Holland, 2003; Thaut, 2010; Pantev and Herholz, 2011; Strait and Kraus, 2011; Miendlarzewska and Trost, 2013; Thaut and Gardiner, 2014; Mansouri et al, 2017). An effect study on music therapy and attention showed improvement in learning skills of patients diagnosed with schizophrenia (Ceccato et al, 2006).…”
Section: Introductionmentioning
confidence: 99%